EFFECT OF THE SOWING DATE AND CHEMICAL CONTROL ON THE ASIAN SOYBEAN RUST, POWDERY MILDEW AND END OF SEASON DISEASES ON SOYBEAN CROP (Revista de Ciências Agroveterinárias, 2005)
More than a hundred diseases affect the soybean crop. The end of season diseases, powdery mildew, and recently the Asian rust (Phakopsora pachyrhizi) occur with high frequence. High losses of grain yield are caused by Asian rust, mainly when early infections occur in the crop cycle. The powdery mildew and end of season diseases generally caused small yield reduction. The present work aimed to evaluate the disease severity, fungicides efficiency and grain yield of soybean in two sowing dates. The end of season diseases and Asian rust presented low severity (less then 1%) due to adverse climatic conditions for their development and they did not decrease grain yield. On the other hand, powdery mildew presented high severity, reaching up to 41%, but without causing yield reduction.
Keywords: Glycine max; fungicides; epidemiology; yield; yield components.